PERAN KEPEMIMPINAN PEMBELAJARAN DALAM OPTIMALISASI MEDIA DIGITAL BERBASIS KOMUNITAS BELAJAR DI SMP BIRRUL WALIDAIN MUHAMMADIYAH PLUPUH - Setyo Nugroho; Wawan Suranto; Darsinah; Wafrotur Rohmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the role of instructional leadership in optimizing the use of digital media supported by the presence of learning communities at SMP Birrul Walidain Muhammadiyah Plupuh. The transformation of 21st-century learning requires schools to integrate technology effectively, positioning principals not only as administrative managers but also as instructional leaders who can initiate, facilitate, and direct the enhancement of teachers’ digital competence. Learning communities function as collaborative platforms where teachers share best practices, engage in reflection, and strengthen their ability to utilize digital media in a sustainable manner. The findings reveal that instructional leadership at this school is demonstrated through the provision of training, mentoring, collaborative routines, and monitoring of digital media use in classroom practices. Learning communities significantly reinforce digital transformation initiatives by fostering a culture of mutual learning among teachers and accelerating technological adaptation. These findings highlight that the synergy between instructional leadership and learning communities serves as a key factor in optimizing digital media for 21st-century learning.